Early and Late Pulmonary AMR Show Distinct Profiles; Clinical and Epigenetic Analyses - Agbor-Enoh, S.; Jang, M.; Singh, K.; Tunc, I.; Pirooznia, M.; Seifuddin, F.; Ponor, I.; Levine, D.; Cochrane, A.; Philogene, M.; Mathews, J.; Shah, P.; et al. (The Journal of heart and lung transplantation, 2020)
Antibody-Mediated Rejection (AMR) that occurs latter in the lung transplant (LTx) course show greater risk of chronic lung allograft dysfunction (CLAD) than early AMR. This suggest distinct mechanisms. This study leverages a large cohort and sensitive genomic tools to profile early and late AMR. 435 LTx patients enrolled in two cohort studies were included. Endpoint and measures: CLAD-free survival is defined as being alive and CLAD-free. A committee adjudicated for both AMR and CLAD. Allograft injury at AMR was assessed as FEV1 decline and as plasma donor-derived cell-free DNA-%ddcfDNA, a validated biomarker. Then, bronchoalveolar lavage cells obtained at AMR (n=11) and no rejection control time points were subject to bisulfite sequencing; only AMR that met ISHLT probable AMR criteria was analyzed to reduce heterogeneity. Analyses: AMR was grouped as late (detected beyond 1 year post-transplant) or early AMR to compare donor-specific antibody (DSA) profile, allograft injury, and CLAD-free survival. Sequence reads for AMR and within subject control were compared to identify differentially methylated genes in early and late AMR. Early AMR (n=75) was more common than late AMR (n=47) over the 20 (IQR = 10 - 37) months follow-up. Both showed similar DSA profiles. However, late AMR showed higher FEV1 decline (0.8 L vs. 0.4L, p <0.01), %ddcfDNA (5.2% vs. 2.1%, p < 0.01), and hazard of dying or developing CLAD than early AMR (Figure A). Epigenetic analysis identified distinct gene sets in early (n=1381) or late (n=994) AMR. There were only 264 (10%) overlapping genes. However, these genes were predominantly hypermethylated in early AMR and hypomethylated in late AMR. Pathway enrichment analysis also show distinct mechanisms; complement pathways in early AMR and NK-cells pathways in late AMR (Figure B) Early and late AMR show distinct clinical and molecular profiles, suggesting the need for different treatment strategies. Validation studies are needed and may guide treatment decisions.